ESG Controversy as a Moderator of the Impact of Environmental, Social, and Governance Indicators on High-Profile Companies' Performance in Asia - Saleh, Rahmat; Wulandari, Nurafifah (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2025)
The purpose of this research paper is to analyze the relationship of each en- vironmental, social, and governance (ESG) aspect to the performance of high-profile companies, and the purpose of this study further analyzes the role of moderating ESG controversies on the relationship of every aspect of ESG disclosure to corporate perfor- mance. Application of research observation data, using observations from 2010 to 2019, is a company in an Asian country listed on the Sustainable Stock Exchange, which requires companies to publish and report ESG aspects. This study excludes the period 2020-2024 from the analysis because the global economic crisis due to the COVID-19 pandemic has caused the company to change its priorities. The purposive sampling method was used in this study, obtaining 847 samples of observational data from seven countries in the Asian region. Regression moderation analysis was used to examine the relationship between each aspect of ESG and the performance of high-profile companies with the controversy of ESG as a moderation variable. The study results obtained findings that social and gov- ernance aspects have a positive and significant effect on the performance of high-profile companies. However, environmental aspects were found to be insignificant. The findings of the ESG controversy weaken the relationship between social and governance aspects of high-profile company performance, and the ESG controversy does not moderate the relationship of environmental disclosure to company performance.